Potensi Dan Tantangan Implementasi Fly-By-Wireless Pada Pesawat Komersil - Dalimunthe, Ernando Rizki; Harahap, Irma H A; Astuti, Y (Institut Teknologi Dirgantara Adisutjipto, 2022)
Recently, sophisticated aircraft such as commercial aircraft have more various components than before. This fact causes an impact in increasing wiring complexity and resulting in more weight to the airplane. To replace the cables, wireless mode is applied, which is called wireless avionic intra-communications (WAIC). In this article, several wireless communication protocols are recommended to be used in some application sensors on the aircraft. The sensor application selection on the aircraft is based on the type of communication data required from each sensor and based on the location of the sensor. The recommended protocol for each application is concluded based on the characteristics of the communication protocol such as signal rate and nominal distance.